Students attitudes responses on collaborative google classroom in environmental science - Reni Marlina; Erwina Oktavianty; Husna Amalya Melati; Eka Ariyati (Jurnal Pendidikan Informatika dan Sains, 2021)
This study examines students' reactions to a climate change research-based lecture delivered via Google Classroom. Lesson study in two cycles is the lecture's context (plan, do, see). This study involved 90 students from three study programs in education faculty at University Tanjungpura Pontianak, including physics education, biology education, and chemical education, who took an environment-based course. The attitude questionnaire was employed in this research. Data is analyzed using a descriptive statistical analysis technique that employs the percentage formula. According to the data analysis, pupils respond positively to the environment study based on climate change research conducted through Google Classroom. As a result, the use of Google Classroom in a lecture setting based on climate change research findings.